The Dates of Birth of Henry VIII’s English Wives - Conor Byrne (Royal Studies Journal, 2021)
Despite holding an enduring place in the modern cultural imagination, the six wives of Henry VIII (r. 1509–1547) remain, in some respects, shadowy figures. This is especially true with regards to their births and childhoods. Controversy surrounds the dates of birth for Anne Boleyn, Jane Seymour, Katherine Howard, and Katherine Parr. Historians have debated extensively the most plausible years in which these four queens may have been born. This article offers a re-assessment of the dates of birth of these four English queens consort by drawing on a wide range of primary evidence, including chronicles, religious treatises, wills, ambassadors’ reports, letters, and portraiture, analysed within the context of sixteenth-century attitudes to marriage, the life cycle, and sexuality. Its conclusions are also informed by an awareness of Henry VIII’s profound concerns about the continuation of the Tudor dynasty, and how this affected his marital selections in 1527, 1536, 1540, and 1543.